Cities and neuroscience research: A systematic literature review - Ancora, Leonardo A.; Blanco-Mora, Diego Andrés; Alves, Inês; Bonifácio, Ana; Morgado, Paulo; Miranda, Bruno (Frontiers in Psychiatry, 2022)
Background: Cities are becoming the socio-economic hubs for the majority of the population as a growing trend. Understanding how our surroundings can mentally affect our everyday life has become crucial to establishing an urban paradigm sustainable for the individuals. The present review aims to explore the empirical studies investigating neural mechanisms underlying cognitive and emotional processes, as well as the risk of developing mental disorders, related to the natural and built urban environment exposure. Moreover, it also attempts to transform the evidence-based knowledge into recommendations for research policy-making, in order to achieve healthier and sustainable cities. Methods: By following the PRISMA framework, a cross-disciplinary team conducted a structured search on PubMed, ProQuest, Web of Science, and Scopus databases, considering only the articles related to how urban environmental exposure affects brain activity and development through objective measurement. Inclusion criteria were studies about the human adult populations, peer-reviewed and in English language (no publication time restrictions). Results: Sixty-four articles that met the inclusion criteria passed through a qualitative assessment and were analyzed to determine the emerging concepts. Overall, the results suggest that green spaces are related to positive mood, stress reduction, and attention restoration. Furthermore, an urban upbringing has been found to affect social evaluative stress processing and air pollution exposure can exacerbate age-related cognitive disorders. Conclusion: Natural spaces are important allies against urban stressors, along with infrastructural features which may affect memory and orientation. As the majority of experiments were conducted using healthy volunteers, a specific focus should be directed towards the clinical and elderly population.